Biomass burning aerosol characteristics for different vegetation types in different aging periods. (May 2019) - Shi, Shuaiyi; Cheng, Tianhai; Gu, Xingfa; Guo, Hong; Wu, Yu; Wang, Ying
Abstract: Eighteen years of sun/sky photometer measurements at seven worldwide AErosol RObotic NETwork (AERONET) sites in typical biomass burning regions were used in this research. The AERONET measurements were analyzed with the help of Moderate-resolution Imaging Spectroradiometer (MODIS) fire products and the HYbrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model. The variation in the physicochemical and optical properties of biomass burning aerosols (BBAs), as well as their shortwave radiative forcing, was revealed for different vegetation types in different aging periods. The result indicated that, with aerosol aging, the BBA characteristics have a non-negligible evolution trend with obvious clustering features for different burning vegetation types. During the aging process, the volume fraction of black carbon (BC) declined (with a maximum drop of 38%) accompanied by particle size growth (with a maximum increment of 0.017 μm). Driven by the change in physicochemical properties, the Single Scattering Albedo (SSA) and the asymmetry factor increased as the aerosol aged (with maximum increments of 0.026 and 0.018 for the SSA and asymmetry factor respectively). The grass and shrub type had a higher volume fraction of BC (2.5 times higher than that in the forest and peat type) and a smaller fine mode volume median radius (with a difference of 0.037 μm from that of the forest and peat type). Such a phenomenon results in a lower SSA (with a difference of 0.103) and asymmetry factor (with a difference of 0.035) in the grass and shrub type when compared to the forest and peat type. Negative (−74 to −30 W/m 2 ) clear-sky top of atmosphere (TOA) shortwave radiative forcing, strengthened during the aging process, was generally found for BBA. The BBA in the forest and peat region usually had stronger negative radiative forcing efficiency. Graphical abstract: Unlabelled Image Highlights: A unified and systematic study of the properties and radiative forcing effect of Biomass Burning Aerosol (BBA) is conducted The AERONET measurements are analyzed with the help of MODIS fire products and HYSPLIT model to ensure analysis quality BBA properties and radiative forcing effect evolve during transport process Significant differences exist between BBAs from different burning vegetation regions Negative clear-sky TOA shortwave radiative forcing, strengthened during the aging process, was generally found for BBA